Socioemotional wealth and performance in private family firms - Razzak, Mohammad Rezaur; Abu Bakar, Raida; Mustamil, Norizah (Emerald, 2019)
Purpose: Socioemotional wealth (SEW) has emerged as a defining concept that distinguishes family-owned business organizations from businesses that are not exclusively controlled by family coalitions. This empirical study expands the literature by presenting a more nuanced understanding of how individual dimensions of socioemotional wealth interacts with firm performance outcomes. Deploying the stakeholder theory, the purpose of this study is to propose a research model linking the five dimensions of SEW with firm performance to propose and test a set of hypotheses. Design/methodology/approach: To test the hypotheses, data were collected through a survey of 357 medium-to-large private family firms in Bangladesh that were involved in export-oriented production of ready-made garments. Based on structural equation modeling, the data were analyzed using SmartPLS. Findings: The results indicate that out of the five dimensions of SEW, three dimensions – family identification, emotional attachment and renewal of bonds through dynastic succession – have a positive and significant impact on firm performance. On the other hand, family control and influence have a significant but negative impact on firm performance. The only exception is in the case of binding social ties, which indicate a non-significant relationship. Research limitations/implications: By attempting to provide a clearer and predictable link between family-centric non-economic goals and firm-centric business goals, the study contributes to theory building and attempts to address the conflict in the literature in the study of family involvement in management and performance of the business enterprise. Practical implications: For industry practitioners and family business owners, it could provide guidance on which family-centric goals would maximize benefits to the firm and address the family-based utilities. Future strategic plans aimed at growth and sustainability of family firms can derive important clues from the findings of this study and design actionable goals that leverage those dimensions of socioemotional wealth that have a positive impact on firm performance. Social implications: Social implications of ensuring survival of family businesses are significant because of their role as one of the largest sources of employment generation in most societies. Policymakers and regulatory authorities would be able to frame customized initiatives to foster growth and sustainability of family enterprises that have such large impact on the economy. Originality/value: Theoretical contribution of the study comes from a more nuanced understanding of relationships between the individual dimension of SEW and firm performance, which will delineate a more consistent and predictable link between family-centric goals and firm-level outcomes. From the perspective of practical contribution, this may provide useful guidelines to industry practitioners and policymakers to frame initiatives that enable growth and sustainability of family firms that are typically the largest employment generators in most economies. © 2019, Emerald Publishing Limited.